Analysis of Students Chemistry Laboratory Literacy in High School - Mutiah, Mutiah; Junaidi, Eka; Irawan, Jono (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research aims to identify the laboratory literacy level of SMA/MA students in Mataram City and describe laboratory literacy in 4 aspects: context, content, competence, and attitude, in carrying out practicums in the laboratory. Laboratory literacy measurement techniques through stages pre-lab to measure the ability of the content aspect, namely identifying knowledge initial or basic concepts that support practicum, subsequent stage lab work to measure context aspects, namely problem identification, analysis objectives, and principles of analytical methods for testing scientific ideas, and attitude aspects during practicum. Stagepost lab measuring competency aspects related to data analysis from practicum results as a basis for decision making. The research data was analyzed descriptively. Research results show that value. The average student laboratory literacy in the context and attitude aspects is high, namely 78.22 and 86.8, but for the content and competency aspects, it is still low, namely 54.26 and 54.15. The conclusions of this research are as follows: (1)Ability The average laboratory literacy of SMA/MA students in the city of Mataram is a category enough, namely 67.71. (2) The ability to apply chemistry to real-life problems (Chemical Literacy) can be improved by optimizing the use of laboratories as chemistry learning centers